Nanostructured hybrid iron-zeolite catalysts

By using hybrid iron nanoparticle catalysts, the problem of difficulty in improving the selectivity and yield of C2-C4 olefins in the prior art is solved, and the efficient Fischer-Tropsch reaction is achieved, which significantly improves the conversion efficiency and yield of C2-C4 olefins.

JP7661331B2Active Publication Date: 2025-04-14AGENCY FOR SCI TECH & RES +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022533070
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-03
Filing Date
2020-12-03
Publication Date
2025-04-14
Estimated Expiration
2040-12-03

AI Technical Summary

Technical Problem

During the Fischer-Tropsch to olefin (FTO), it is difficult for existing iron-based catalysts to simultaneously increase the selectivity and yield of C2-C4 olefins while inhibiting the formation of C5+.

Method used

A hybrid iron nanoparticle catalyst is used, which consists of 30-70 wt% iron nanoparticles and 30-70 wt% aluminosilicate or silicon-aluminophosphate-based lithoplasmic catalysts. The diameter of the nanoparticles is between 2-50 nm and is prepared by one-handed deposition and physical mixing methods.

Benefits of technology

This catalyst significantly improves the selectivity and yield of C2-C4 olefins in the Fischer-Tropsch reaction, shortens the activation time, and improves the photoolefin conversion efficiency of 24 mol%C compared with traditional catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661331000006
    Figure 0007661331000006
  • Figure 0007661331000007
    Figure 0007661331000007
  • Figure 0007661331000008
    Figure 0007661331000008
Patent Text Reader

Abstract

The hybrid iron nanoparticle catalyst of the present invention comprises: (i) nanoparticles comprising iron and at least one metal M selected from the group consisting of alkali metals, alkaline earth metals, transition metal elements of Groups 3 to 7 and 9 to 11 of the periodic table, lanthanides, and combinations thereof, in an amount of 1 to 50 wt.% based on the total weight of the catalyst; and (ii) an aluminosilicate or silicoaluminophosphate zeolite in an amount of 50 to 99 wt.% based on the total weight of the catalyst, wherein the nanoparticles have a diameter of about 2 to 50 nm. The present invention further relates to a method for preparing the hybrid iron nanoparticle catalyst and a process for producing light olefins using the hybrid iron nanoparticle catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the synthesis of nanostructured hybrid Fe-zeolite catalysts that can optimize the selectivity and yield of light olefins. A specific example is carried out by one-pot precipitation reaction and physical mixing with zeolite. [Background technology]

[0002] Fischer-Tropsch synthesis is a series of chemical processes that use CO and H2 as feedstocks to produce long-chain hydrocarbons. These processes are typically carried out over Co, Fe, Ru, and even Ni and Re-based catalysts. However, traditional catalysts and processes are known to produce low yields of light olefins, mainly from paraffins and / or gasoline products.

[0003] In recent years, the direct Fischer-Tropsch to olefin (FTO) process using Fe has attracted attention due to its low cost compared to other materials and promising selectivity to light olefin products (C2-C4). In particular, Fe-based catalysts promoted with elements such as alkali metals, alkaline earth metals, transition metals, and lanthanides exhibit various properties, such as dispersion of active sites, faster activation, suppression of methane, and improvement of olefinicity of hydrocarbon products. Summary of the Invention [Problem to be solved by the invention]

[0004] A highly efficient iron-based catalyst for FTO is required to have high selectivity for light olefins and low selectivity for CH4 and C5+ (hydrocarbons with 5 or more carbons). However, conventional iron-based catalysts can only produce mainly paraffin and / or gasoline products. Moreover, for known Fe-based catalysts, the product distribution is limited by the so-called Anderson-Schulz-Flory (ASF) theory, which shows that it is difficult to maximize the selectivity of C2-C4 olefins while suppressing the increase in selectivity of CH4 and / or C5+.

[0005] Thus, there is a need for catalysts and methods of using catalysts that overcome or ameliorate one or more of the above-mentioned shortcomings. [Means for solving the problem]

[0006] One aspect of the present invention provides a hybrid iron nanoparticle catalyst, the hybrid iron nanoparticle catalyst comprising: i) 30 to 70 wt.% of the total weight of the catalyst of nanoparticles comprising iron and at least one metal M selected from the group consisting of alkali metals, alkaline earth metals, transition metal elements of groups 3 to 7 and 9 to 11 of the periodic table, lanthanides and combinations of these elements; ii) 70 to 30 wt.% of an aluminosilicate or silicoaluminophosphate zeolite based on the total weight of the catalyst; The diameter of the nanoparticles is about 2-50 nm, and the total weight percentage of the nanoparticles and zeolite is 100 wt.%.

[0007] Furthermore, the hybrid iron nanoparticle catalysts described above may exhibit improved activity over Fischer-Tropsch iron catalysts known in the art. High selectivity and conversion of gases having hydrogen and carbon oxides to desired light olefins may be achieved utilizing the catalysts described herein. This is believed to be due to the high proportion of alkali metals, alkaline earth metals, transition metals, or lanthanides in the catalyst and the porous structure of the zeolite.

[0008] For example, the catalysts described above may have a spinel crystal phase.

[0009] Furthermore, nanoparticle catalysts with a spinel phase can improve the conversion efficiency of carbon monoxide or carbon dioxide to light olefins, especially the conversion efficiency to light olefins containing 2 to 4 carbon atoms, which was improved by up to 24 mol.C% compared to conventional catalysts. The improved yield is believed to be due to the crystalline spinel phase of the nanoparticle catalyst.

[0010] In another aspect, a method for preparing a hybrid nanoparticle iron catalyst is provided, comprising: i) mixing a solution containing an iron salt with an aqueous surfactant to form a mixture; ii) adding a basic salt solution comprising a salt of an element selected from the group consisting of alkali metals, alkaline earth metals, transition metal elements of groups 3 to 7 or 9 to 11 of the periodic table, lanthanides, and combinations thereof, to the mixture of step (i) to produce a precipitate; iii) heating the precipitate of step (ii) in the presence of air and oxygen; iv) Mixing the precipitate of step (iii) with an aluminosilicate or silicoaluminophosphate zeolite to obtain a hybrid iron catalyst.

[0011] Furthermore, the above-mentioned method for preparing the hybrid iron nanoparticle catalyst may involve co-precipitation of the iron nanoparticle catalyst with a basic salt solution. The co-precipitation method may allow for high concentrations of alkali metals, alkaline earth metals, transition metal elements from groups 3 to 7 or 9 to 11 of the periodic table, lanthanides, and combinations of these elements in the nanoparticles. Such iron nanoparticles have surprisingly been shown to enhance the catalytic activity of the conversion of carbon monoxide or carbon dioxide to light olefins via the Fischer-Tropsch reaction. According to the improvement in the conversion of carbon monoxide or carbon dioxide gas, the catalyst may also show selectivity for light olefins containing 2 to 4 carbon atoms over methane and long chain paraffins.

[0012] Additionally, the hybrid iron catalysts and zeolites described herein can reduce the catalyst activation time in the Fischer-Tropsch reaction, i.e., activation rates of 2-16 hours compared to 40-100 hours for conventional catalysts. Thus, high yields of light olefins can be achieved in a short time without compromising the selectivity of the catalyst to C2-C4 light olefins.

[0013] In another aspect, a process for producing light olefins is provided, comprising: i) heating the catalyst as defined above in the presence of a gas comprising one or more oxides of carbon and hydrogen to activate said catalyst; ii) contacting the catalyst activated in step (i) with a gaseous stream comprising one or more carbon oxides and hydrogen to partially or completely convert the one or more carbon oxides to the light olefins, the light olefins comprising from 2 to 4 carbon atoms; Methane is substantially absent from the light olefins or constitutes less than 20% of the light olefins.

[0014] Additionally, the process may achieve high conversion efficiencies of carbon oxides to hydrocarbons with the presently disclosed catalysts. In particular, the catalysts described herein excel at forming short chain olefins over paraffins, particularly light olefins containing 2-4 carbon atoms. Such light olefins are selectively produced from methane using the presently disclosed iron-zeolite catalysts. The high conversion efficiency and selectivity of the iron-zeolite catalyst in the disclosed process is believed to be due to the spinel phase of the iron nanoparticles that are particularly active in the production of light olefins from carbon oxides. Additionally, the zeolite present in the catalyst may act to crack C5+ olefins and improve the selectivity of the catalyst to light olefins.

[0015] Surprisingly, the iron-zeolite catalyst may have a shorter activation time in the disclosed process compared to similar iron-zeolite catalysts known in the art, which may enable high yields of light olefins to be obtained in even shorter reaction times.

[0016] <Definition> As used herein, the following words and terms have the meanings indicated below. "Promoted" as used herein refers to activation of catalytic activity or significant change in catalytic properties of a catalyst in the presence of additional metal ions, preferably selected from the group consisting of alkali metals, alkaline earth metals, transition metals from groups 3 to 7 or 9 to 11 of the periodic table, or lanthanides, and combinations of these elements. "Promotion" and "promoter" have similar meanings.

[0017] "Spinel crystal phase" herein refers to minerals of the general composition type AB2X4, which contain X anions (generally Group 16 elements including oxygen and sulfur) arranged in cubic close packing, and cations A and B occupying some or all of the lattice sites of the octahedra and tetrahedra.

[0018] "Light olefins" as used herein refer to olefins or alkenes containing 2 to 4 carbon atoms. Light olefins may refer to, i.e., methylene, propene, and / or butenes. That is, butenes may include but-l-ene, (2Z)-but-2-ene, (2E)-but-2-ene, and 2-methylprop-1-ene.

[0019] "Substantially" does not exclude "completely". A composition that is "substantially free" of Y may be completely free of Y. If necessary, the term "substantially" may be omitted from the definition of the invention.

[0020] Unless otherwise noted, the terms "including" and "comprising" and their grammatical variations are intended to be "open" or "inclusive" in nature, including the recited elements, but which may include additional or unrecited elements. Unless otherwise specified, "About" in the context of an ingredient concentration herein typically refers to + / - 5% of the stated value, more typically + / - 4% of the stated value, more typically + / - 3% of the stated value, more typically + / - 2% of the stated value, even more typically + / - 1% of the stated value, and even more typically + / - 0.5% of the stated value.

[0021] Throughout this specification, certain embodiments may be described in a range format. It should be understood that the description in range format is merely for convenience and brevity, and the disclosed ranges should not be interpreted as inflexible limitations. Thus, the description of a range should be considered to specifically disclose all possible subranges and individual numerical values ​​within that range. For example, the range of 1 to 6 should be considered to specifically disclose the subranges 1 to 3, 1 to 4, 1 to 5, 2 to 4, 2 to 6, 3 to 6, etc., and the individual numerical values ​​(e.g., 1, 2, 3, 4, 5, and 6) contained within that range. This applies regardless of the width of the range.

[0022] Certain embodiments may also be described broadly and generically herein. Narrower species and subgeneric groupings included in the generic disclosure are also part of the disclosure, i.e., this includes a generic disclosure of embodiments with a proviso or negative limitation removing any subject matter from the genus, whether or not the removed subject matter is specifically described herein. Certain embodiments may also be broadly and generically described herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The catalyst and process proposed herein combines zeolite with nanostructured hybrid Fe-zeolite catalyst through physical mixing to enhance activity, selectivity and yield of light olefins.

[0024] In particular, the present disclosure relates to a method for the synthesis of promoted nanoparticulate iron-based catalysts for the Fischer-Tropsch reaction to afford C2-C4 linear alpha olefins in high yields up to 20 Cmol.% per pass.

[0025] The catalyst proposed herein comprises nanoparticles comprising iron and at least one metal M selected from the group consisting of alkali metals, alkaline earth metals, transition metal elements from groups 3 to 7 or 9 to 11 of the periodic table, lanthanides and combinations of these elements, in an amount of 30 to 70 wt.% of the total weight of the catalyst, and an aluminosilicate or silicoaluminophosphate zeolite in an amount of 70 to 30 wt.% of the total weight of the catalyst, the diameter of said nanoparticles being about 2-50 nm, and the total weight percentage of said nanoparticles and zeolite being 100 wt.%.

[0026] The catalyst may comprise about 30 to about 70 wt.%, about 30 to about 40 wt.%, about 30 to about 50 wt.%, about 30 to about 60 wt.%, about 40 to about 50 wt.%, about 40 to about 60 wt.%, about 40 to about 70 wt.%, about 50 to about 60 wt.%, about 50 to about 70 wt.%, or about 60 to about 80 wt.% nanoparticles. The catalyst may comprise about 30 to about 70 wt.%, about 30 to about 40 wt.%, about 30 to about 50 wt.%, about 30 to about 60 wt.%, about 40 to about 50 wt.%, about 40 to about 60 wt.%, about 40 to about 70 wt.%, about 50 to about 60 wt.%, about 50 to about 70 wt.%, or about 60 to about 80 wt.% zeolite.

[0027] The total weight of nanoparticles and zeolite is 100 wt.%.

[0028] The diameter of the nanoparticles may range from about 2 nm to about 50 nm, about 2 nm to about 5 nm, about 2 nm to about 10 nm, about 2 nm to about 20 nm, about 5 nm to about 10 nm, about 5 nm to about 20 nm, about 5 nm to about 50 nm, about 10 nm to about 20 nm, about 10 nm to about 50 nm, or about 20 nm to about 50 nm.

[0029] The metal M may comprise about 10 to 50 wt.%, or about 10 to about 20 wt.%, about 10 to about 30 wt.%, about 10 to about 40 wt.%, about 20 to about 30 wt.%, about 20 to about 40 wt.%, about 20 to about 50 wt.%, about 30 to about 40 wt.%, about 30 to about 50 wt.%, or about 40 to about 50 wt.%, more preferably about 10% of the weight of the iron nanoparticles.

[0030] The nanoparticles may have a spinel crystalline phase.

[0031] The chemical formula of the catalyst having a spinel crystal phase may have the formula FeM2O4.

[0032] The metal M may be selected from the group consisting of alkali metals, alkaline earth metals, transition metal elements from groups 3 to 7 or 9 to 11 of the periodic table, lanthanides, and combinations of M. The alkali metals may be selected from the group consisting of lithium, sodium, potassium, rubidium, and cesium. The alkaline earth metals may be selected from the group consisting of beryllium, magnesium, calcium, strontium, and barium. The group 3 elements may be selected from the group consisting of scandium and yttrium. The group 4 elements may be selected from the group consisting of titanium, zirconium, and hafnium. The group 5 elements may be selected from the group consisting of vanadium, niobium, and tantalum. The group 6 elements may be selected from the group consisting of chromium, molybdenum, and tungsten. The group 7 elements may be selected from the group consisting of manganese, technetium, and rhenium. The group 9 elements may be selected from the group consisting of cobalt, rhodium, and iridium. The group 10 element may be selected from the group consisting of nickel, palladium and platinum. The group 11 element may be selected from the group consisting of copper, silver and gold. The lanthanides may be selected from the group consisting of lanthanum, cerium, praseodymium, neodymium, promethium, samanium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium.

[0033] The metal M may be an alkali metal. The metal M may be sodium.

[0034] The zeolite may be an aluminosilicate zeolite. The zeolite may be a pentasil or faujasite zeolite. The zeolite may be selected from the group consisting of zeolite X, ZSM-5, zeolite Y, ZSM-12, ZSM-22, and HY zeolite. The zeolite may be ZSM-5, or HY zeolite.

[0035] ZSM-5 has the chemical formula Na n Al n S96-n O 192 ·16H₂O (0 < n < 27) may be present, zeolite Y may have the chemical formula Al₂O₅Si, ZSM-12 may have the chemical formula |Na x (H₂O)₄|₂[Al x Si 28-x O 56 ₂-(x < 2.5) may be present, ZSM-22 may have the chemical formula |Na n (H₂O)₄|[Al x Si 24-x O 48 (x < 2) may be present. Both zeolite X and Y may have the same basic chemical formula |(Ca,Mg,Na₂) 29 (H₂O) 240 |[Al 58 Si 134 O 384 . Further, Y may have a Si / Al ratio of 1.5 times. Zeolite HY may be a H⁺-form zeolite Y in which Ca, Mg or Na is substituted. The molar ratio of alumina to silica in the zeolite may be from about 1:2 to about 1:90, or from about 1:5 to about 1:90, or from about 1:10 to about 1:90, or from about 1:15 to about 1:90, or from about 1:20 to about 1:90, or from about 1:25 to about 1:90, or from about 1:30 to about 1:90, or from about 1:35 to about 1:90, or from about 1:40 to about 1:90, or from about 1:45 to about 1:90, or from about 1:50 to about 1:90, or from about 1:55 to about 1:90, or from about 1:60 to about 1:90, or from about 1:65 to about 1:90, or from about 1:70 to about 1:90, or from about 1:75 to about 1:90, or from about 1:75 to about 1:85, or more preferably about 1:80.

[0036] The zeolite may be a silicoaluminophosphate zeolite. The silicoaluminophosphate may be SAPO11 or SAPO34. SAPO11 may have the chemical formula H x Si x Al 20 P 20-x O 80(x=0 to 4), SAPO34 The chemical formula is Ca6(H2O) 40 | 1 / 3 [Al 12 S 24 O 72 ] 1 / 3

[0043] The weight ratio of zeolite to iron nanoparticles may be from about 1:0.5 to about 1:10, or from about 1:0.5 to about 1:8, or from about 1:0.5 to about 1:6, or from about 1:0.5 to about 1:4, or from about 1:0.5 to about 1:3, or from about 1:0.5 to about 1:2, or more preferably about 1:1.

[0037] The iron nanoparticles may further comprise a halogen oxide, the halogen being bromine.

[0038] The halogen oxide may be present in an amount of about 0.1 to about 50 wt.%, or about 0.1 to about 45 wt.%, or about 0.1 to about 40 wt.%, or about 0.1 to about 35 wt.%, or about 0.1 to about 30 wt.%, or about 0.1 to about 25 wt.%, or about 0.1 to about 20 wt.% of the weight of the nanoparticles.

[0039] Iron nanoparticles may exhibit an X-ray diffraction pattern with prominent diffraction peaks at 2θ=29.5°, 35°, 37°, 42.5°, 56.2°, and 62°, as shown in FIG. 2B.

[0040] The iron nanoparticle catalyst may exhibit the extended X-ray absorption fine structure spectrum shown in FIG. 3. The Fe-O coordination peak (308) may be seen at a radial distance of 1.4 Å, and the first Fe-Fe coordination peak (310) may be seen at 2.6 Å. The second Fe-Fe coordination peak (312) may be seen at around 3.1 Å, which is a typical peak for Fe3O4 (304) and exists as a shoulder for Fe2O3 (306) due to the lack of Fe in the chemical composition. The lack of a peak for FeNa (Fe2O3-Na) (302) suggests that it has the formula FeNa2O4, i.e., the Fe atom is replaced by a Na atom. In this description, FeNa may be interchangeable with Fe2O3-Na.

[0041] The iron nanoparticles may further comprise a transition metal element from groups 3 to 7 or 9 to 11 of the periodic table. The transition metal may be selected from groups 7 or 10. The transition metal may be manganese.

[0042] The molar ratio of iron to transition metal can be from about 1:1 to about 50:1, or from about 1:1 to about 40:1, or from about 1:1 to about 30:1, or from about 1:1 to about 20:1, or from about 1:1 to about 18:1, or from about 1:1 to about 16:1, or from about 1:1 to about 14:1, or from about 1:1 to about 12:1, or from about 2:1 to about 12:1, or from about 3:1 to about 12:1, or from about 4:1 to about 12:1, or from about 5:1 to about 12:1, or from about 6:1 to about 12:1, or from about 8:1 to about 12:1, or from about 8:1 to about 10:1, and more preferably about 9:1.

[0043] The iron nanoparticles may further comprise a SiO2 matrix.

[0044] Further provided is a method for preparing a hybrid nanoparticle iron catalyst, comprising the steps of: mixing a solution comprising an iron salt with an aqueous surfactant to form a mixture; adding a basic salt solution comprising a salt of an element selected from the group consisting of alkali metals, alkaline earth metals, transition metal elements from groups 3 to 7 or 9 to 11 of the periodic table, lanthanides, and combinations thereof, to the mixture of step (i) to form a precipitate; heating the precipitate of step (ii) in the presence of air and oxygen; and mixing the precipitate of step (iii) with an aluminosilicate or silicoaluminophosphate zeolite to obtain the hybrid iron catalyst.

[0045] The salts of the elements may include hydroxide, carbonate or bicarbonate anions.

[0046] The salts of the elements may include alkali metal cations.

[0047] The salt of the element may be a sodium salt.

[0048] The molar ratio of iron to the basic salt element may be from about 1:2 to about 1:25, preferably from about 1:2 to about 1:20, or from about 1:2 to about 1:18, or from about 1:2 to about 1:16, or from about 1:2 to about 1:15, or from about 1:2 to about 1:14, or from about 1:2 to about 1:13, or from about 1:2 to about 1:12, or from about 1:2 to about 1:11, or from about 1:2 to about 1:10, or from about 1:3 to about 1:10, more preferably from about 1:4 to 1:10.

[0049] The molar ratio of alumina to silica in the zeolite may be from about 1:2 to about 1:90, or from about 1:5 to about 1:90, or from about 1:10 to about 1:90, or from about 1:15 to about 1:90, or from about 1:20 to about 1:90, or from about 1:25 to about 1:90, or from about 1:30 to about 1:90, or from about 1:35 to about 1:90, or from about 1:40 to about 1:90, or from about 1:45 to about 1:90, or from about 1:50 to about 1:90, or from about 1:55 to about 1:90, or from about 1:60 to about 1:90, or from about 1:65 to about 1:90, or from about 1:70 to about 1:90, or from about 1:75 to about 1:90, or from about 1:75 to about 1:85, or more preferably about 1:80.

[0050] The heating step may be carried out at a temperature of about 300°C to about 600°C, or about 350°C to about 600°C, or about 400°C to about 600°C, or about 450°C to about 600°C, or about 500°C to about 600°C, or about 500°C to about 580°C, or about 500°C to about 560°C, or about 500°C to about 550°C, more preferably about 550°C.

[0051] The heating step may be carried out for about 1 to about 10 hours, or about 1 to about 8 hours, or about 1 to about 6 hours, or about 1 to about 5 hours, or about 1 to about 4 hours, or about 1 to about 3 hours, or about 1 to about 2 hours, more preferably about 2 hours.

[0052] The iron salt may be a divalent iron salt or a trivalent iron salt.

[0053] The iron salt may comprise an anion selected from the group consisting of nitrate, chloride, fluoride, bromide, iodide, phosphate, pyrophosphate and perchlorate.

[0054] The iron salt may be ferric nitrate.

[0055] The surfactant may be an ionic surfactant. The surfactant may comprise an anion selected from the group consisting of halides, sulfonates, sulfates, phosphates and carboxylates.

[0056] The surfactant comprises a halide anion. The surfactant comprises a fluoride, chloride, bromide or iodide anion.

[0057] The surfactant comprises a bromide anion.

[0058] The surfactants are cetrimonium bromide, pluronic F-127, which has the chemical formula (C3H6O·C2H4O)x, and C 2n H 4n+2 O n+1 (n=8.2 to 9.1), and mixtures thereof. The molar ratio of iron to surfactant may be from about 1:0.5 to about 1:15, or from about 1:0.5 to about 1:12, or from about 1:0.5 to about 1:10, or from about 1:0.5 to about 1:8, or from about 1:0.5 to about 1:6, or from about 1:0.5 to about 1:4, or from about 1:0.5 to about 1:2, or more preferably about 1:1.

[0059] The method may further comprise, prior to step (iii), recovering the precipitated nanoparticle catalyst and drying the precipitated nanoparticle catalyst in air.

[0060] Recovery of the precipitated nanoparticle catalyst may be accomplished by centrifugation and / or filtration.

[0061] The method may further comprise the step of adding a solution of a salt of a transition metal to the mixture of step (i) prior to step (ii).

[0062] The molar ratio of iron to transition metal may be from about 1:1 to about 50:1, or from about 1:1 to about 40:1, or from about 1:1 to about 30:1, or from about 1:1 to about 20:1, or from about 1:1 to about 18:1, or from about 1:1 to about 16:1, or from about 1:1 to about 14:1, or from about 1:1 to about 12:1, or from about 2:1 to about 12:1, or from about 3:1 to about 12:1, or from about 4:1 to about 12:1, or from about 5:1 to about 12:1, or from about 6:1 to about 12:1, or from about 8:1 to about 12:1, or from about 8:1 to about 10:1, more preferably about 9:1.

[0063] The method may further comprise introducing the mixture of step (i) into a solution of the silicate prior to step ii).

[0064] The silicate may contain alkoxy groups of 2 to 15 carbon atoms, preferably 2 to 12 carbon atoms, 2 to 10 carbon atoms, or 2 to 8 carbon atoms, or 2 to 6 carbon atoms, or 2 to 5 carbon atoms. The silicate may be tetraethyl orthosilicate.

[0065] The molar ratio of iron to said silicate may be from about 1:1 to about 1:50, or from about 1:1 to about 1:45, or from about 1:1 to about 1:40, or from about 1:1 to about 1:35, or from about 1:1 to about 1:30, or from about 1:1 to about 1:25, or from about 1:1 to about 1:20, or from about 1:1 to about 1:18, or from about 1:1 to about 1:16, or from about 1:1 to about 1:15, or from about 1:1 to about 1:12, or from about 1:2 to about 1:12, more preferably from about 1:5 to about 1:12.

[0066] The catalyst as defined above may be prepared by the method as defined above. In a particular example, a one-pot synthesis method for iron-based nanoparticle catalysts promoted with metals such as Na, Mn and Ni is provided. The method involves mixing an aqueous solution of iron salt (e.g. Fe(NO)3)3) with a surfactant (e.g. cetyltrimethylammonium bromide (CTAB)) in pure water, followed by precipitation of the Fe phase as Fe(OH)2 with a promoting base (e.g. NaOH). The resulting precipitate, upon calcination in air, results in an Fe spinel phase with an amorphous Na phase. A suitable zeolite, such as HY zeolite, is then physically mixed with the nanostructured iron to produce the hybrid catalyst.

[0067] In another particular example, a one-pot synthesis method for structurally improved sodium-promoted iron-based nanoparticle catalysts is provided. The method involves mixing an aqueous solution of an iron salt (e.g., Fe(NO)3)3 with a surfactant (e.g., CTAB) in pure water. Combine This involves the precipitation of the Fe phase as Fe(OH)2 with a promoting base (e.g. NaOH) followed by the addition of a suitable reagent such as tetraethyl orthosilicate (TEOS) or aluminum isopropoxide (AIP) to form an oxide matrix. When TEOS is added, SiO2 is formed as a structural binder. The resulting precipitate, upon calcination in air, results in an Fe spinel phase (Fe2O3) promoted with an amorphous Na phase supported on an oxide matrix (e.g. SiO2). A suitable zeolite such as HY zeolite is then physically mixed with the nanostructured iron to produce the hybrid catalyst.

[0068] Nanosized Fe particles have shown improved light olefin selectivity and, in combination with high activity, Fe-based Fischer-Tropsch to olefin (FTO) processes can be of industrial interest since they can maximize the light olefin yield per pass. Furthermore, supporting Fe-based catalysts with oxides such as SiO2 and Al2O3 has been shown to improve the stability of their performance.

[0069] Fe-based catalysts have been combined with zeolites for Fischer-Tropsch (FT) synthesis, either as Fe / zeolite-supported systems or as physically mixed Fe+zeolite systems. When used in this way, the combined zeolites (typically ZSM-5) are observed to have gasoline-range product distributions coupled with high paraffin yield selectivity. In particular, iron nanoparticles have a high alkali metal content (~10-20 wt.%), the content of which is influenced by the type of metal hydroxide precipitate (e.g., Fi, Na, K, Cs). For example, Na is incorporated into the iron phase through precipitation, with iron forming a dominant spinel phase that is not identified as Fe3O4 by X-ray diffraction (XRD) and extended X-ray absorption fine structure (EXAFS). In this way, their incorporation into the iron phase has been shown to result in higher than typical alkali metal contents, which results in high catalyst activity and simultaneously high olefinicity.

[0070] Halogen anions present in surfactants act as promoters for iron catalysts, e.g., 1) Br has been shown to suppress Ni hydrogenation, similar to the use of S as a selective poison to enhance olefin selectivity, and 2) Br has been shown to reduce Fe(CO)5 to Fe5C2, the active carbide phase of FTO, and may play a similar role during the dynamic phase changes of Fe-based catalysts during the reaction. Retaining alkali metals and halogens as promoters may reduce the need for further wastewater treatment during industrial synthesis, which may play a relevant role in the cost analysis of FTO technology.

[0071] A process for producing light olefins, i) heating the catalyst as defined above in the presence of a gas comprising one or more oxides of carbon and hydrogen to activate said catalyst; ii) contacting the catalyst activated in step (i) with a gaseous stream comprising one or more carbon oxides and hydrogen to partially or completely convert said one or more carbon oxides to said light olefins; The light olefins contain 2 to 4 carbon atoms, and methane is substantially absent from the light olefins or constitutes less than 20% of the light olefins.

[0072] The carbon oxide may be carbon monoxide (CO) or carbon dioxide (CO2).

[0073] Said step (i) may be carried out at a temperature of from about 200°C to about 350°C, or from about 200°C to about 340°C, or from about 220°C to about 300°C, or from about 230°C to about 300°C, or from about 240°C to about 300°C, or from about 250°C to about 300°C, or from about 260°C to about 300°C, or from about 270°C to about 300°C, or from about 280°C to about 300°C, more preferably at about 290°C.

[0074] Said step (ii) may be carried out at about 200°C to about 450°C, or about 220°C to about 450°C, or about 240°C to about 450°C, or about 260°C to about 450°C, or about 280°C to about 450°C, or about 300°C to about 450°C, or about 300°C to about 420°C, or about 300°C to about 400°C, or about 320°C to about 400°C, or about 330°C to about 400°C, more preferably about 330°C to 390°C.

[0075] Step (i) may be carried out at a pressure of about 5 to about 30 bar, or about 5 to about 25 bar, or about 5 to about 20 bar, or about 5 to about 15 bar, or about 5 to about 10 bar, more preferably about 10 bar.

[0076] Step (ii) may be carried out at a pressure of about 5 to about 50 bar, or about 5 to about 45 bar, or about 5 to about 40 bar, or about 5 to about 35 bar, or about 5 to about 30 bar, or about 5 to about 25 bar, or about 10 to about 25 bar, or about 15 to about 25 bar, more preferably about 20 bar.

[0077] The space velocity of the gas fluid in step (ii) may be from about 1500 ml / gh to about 5000 ml / gh, or from about 1500 ml / gh to about 4500 ml / gh, or from about 1500 ml / gh to about 4000 ml / gh, or from about 1500 ml / gh to about 3500 ml / gh, or from about 1500 ml / gh to about 3000 ml / gh, or from about 1500 ml / gh to about 2500 ml / gh, or more preferably from about 2000 ml / gh to 2500 ml / gh.

[0078] The ratio of hydrogen to one or more carbon oxides in the gas may be from about 4:1 to about 1:3, or from about 3:1 to about 1:3, or from about 2:1 to about 1:3, or from about 2:1 to about 1:2, more preferably about 1:1.

[0079] The process may further comprise, prior to step (i), reducing the catalyst as defined above by contacting the catalyst with a stream of hydrogen gas.

[0080] The carbon oxide of the gaseous stream in step (ii) may be carbon dioxide.

[0081] The conversion of carbon dioxide to hydrocarbon products in the above defined process may be at least 20 mol C%, or at least 30 mol C%, or at least 40 mol C%, or at least 50 mol C%.

[0082] The yield of methane in the product stream resulting from the above defined process may be less than 15%, or less than 10%, or preferably less than 5% in the product gas stream. Additionally, the concentration of carbon monoxide in the product gas stream may be less than 12%, or less than 10%, or less than 8%, or less than 5%, or less than 1%.

[0083] Additionally, the above defined process may provide 2 to 4 carbon element olefin products in an amount of at least 5 mol%, or between 5 and 90%, or between 5 and 85%, or between 5 and 80%, or between 5 and 75%, or between 5 and 70%, or between 5 and 65%, or between 5 and 60%, or between 5 and 55%, or between 5 and 50%, or between 5 and 45%, or at least between 5 and 40%.

[0084] The amount of hydrocarbons containing 2 to 4 carbon elements in the product gas stream may be at least 20 mol%, or at least 25 mol%, or at least 30 mol%, or at least 35%, of which at least 75%, or at least 80%, or at least 85 mol% are olefins containing 2 to 4 carbon elements. [Brief description of the drawings]

[0085] The accompanying drawings illustrate disclosed embodiments and serve to explain the principles of the disclosed embodiments, but it is to be understood that the drawings are designed for illustrative purposes only and not as a definition of the limits of the invention. [Figure 1] Figure 1 shows transmission electron microscope (TEM) images of A) an FeNa sample prepared by precipitation of Fe(NO3)3 with the addition of NaOH (scale bar 20 nm) and B) a magnified image of iron-based particles (scale bar 10 nm). The microstructure consists of small nanoparticles with sizes of 4-5 nm. [Figure 2A] Figure 2A shows the X-ray diffraction (XRD) patterns of FeNa prepared by two methods: the first was prepared at room temperature without aging (202), and the second was aged at 70 °C for 16 h (204). [Figure 2B] FIG. 2B shows the X-ray diffraction (XRD) pattern of FeNa(208) and, for comparison, the simulated pattern of FeNa2O4(208). [Diagram 3]Figure 3 shows the extended X-ray absorption fine structure (EXAFS) spectrum of the FeNa catalyst (Fe2O3-Na) (302), which shows the Fe-O coordination peak (308) and the Fe-Fe coordination peak (310). The Fe-Fe coordination peak lacks the shoulder (312) typically seen in Fe2O3 (306) and Fe3O4 (304). [Figure 4] Figure 4 shows the energy dispersive X-ray analysis (EDS) of FeNa, showing uniform distribution of A) Fe, B) Br, C) Na, and D) O. An EDS map of oxygen is provided as a reference for the distribution of trace elements such as Na and Br. Scalebar is 2.5 μm. [Diagram 5] Figure 5 shows the energy dispersive X-ray analysis (EDS) of FeNa-Mn, showing uniform distribution of A) Fe, B) Br, C) Na, D) Mn, and E) O. An EDS map of oxygen is provided as a reference for the distribution of trace elements such as Na and Br. Scalebar is 2.5 μm. [Figure 6] FIG. 6 shows the X-ray photoelectron spectroscopy (XPS) spectrum of FeNa, indicating the contribution of Br in the catalyst. [Figure 7] Figure 7 is a transmission electron microscope (TEM) image of s-FeNa, showing that the iron-based nanoparticles are well dispersed in the 90 wt.% silica matrix. Scale bar is 10 nm. [Figure 8] Figure 8 shows the light olefin ratio (O / (O+P)) versus CO conversion for FeNa catalysts activated under different conditions. The performance of the catalysts could be improved by parametric optimization. [Figure 9] Figure 9 shows a comparison of long-term stability between FeNa (Fe2O3-Na) and Fe / CNF (carbon nano fibers) as shown in the prior art. The catalyst of the present invention continues to improve in performance after 170 hours, while the performance of the benchmark (prior art) catalyst has fallen to less than half of its initial performance after 100 hours. EXAMPLES

[0086] Non-limiting examples of the present invention are described in further detail by reference to specific examples, which should not be construed as limiting the scope of the invention.

[0087] Example 1: General synthesis Three general classes of catalysts are disclosed below. 1) Hybrid nanostructured Fe-zeolite catalyst As an example, a method for the preparation of hybrid nanostructured Fe-zeolite catalyst is provided herein. The method begins with mixing an iron salt, such as Fe(NO3)3, with deionized H2O along with a surfactant, such as cetyltrimethylammonium bromide (CTAB), to obtain a well-mixed solution. An alkaline base, such as NaOH, is then used to precipitate the iron in solution. The precipitate is collected by centrifugation without washing and dried in air before calcination at 550 °C for 2 h to obtain Fe-based spinel nanoparticles. This method produces Na-promoted nanoparticles of 4-5 nm size in a single precipitation, which eliminates the need for a washing step to remove Na cations and also provides good light olefin (C2-C4) selectivity and yield performance. These nanoparticles are then physically mixed with a zeolite, such as ZSM-5, to form the hybrid catalyst. The hybrid iron oxide catalyst was then activated in syngas at 10 bar and 290 °C for 24 h, and the catalyst performance was followed at 370 °C, 20 bar, and syngas flow with H2 / CO = 1. Where high activity (>90 Cmol.% CO conversion efficiency) was observed, the temperature and / or H2 / CO ratio were adjusted to maximize the light olefin yield.

[0088] 2) X-promoted hybrid nanostructured Fe-zeolite catalysts As another example, a method for preparing X-promoted hybrid nanostructured Fe-zeolite catalysts is provided herein, where X=Ni, Mn, Mg, Ca, La, Co, Li, K, Ce, or combinations thereof. The method for preparing nanosized Fe-based catalysts begins with mixing an iron salt, such as Fe(NO3)3, and a promoting salt, such as Mn(NO3)2, with deionized H2O along with a surfactant, such as CTAB, to obtain a well-mixed solution. An alkaline base, such as NaOH, is then used to precipitate the iron in solution. The precipitate is collected by centrifugation without washing and dried in air before calcination at 500°C for at least 2 or 5 hours to obtain Fe-based spinel nanoparticles. This method produces 4-5 nm sized X-promoted nanoparticles in a single precipitation, eliminating the need for a washing step to remove the X cations, and can provide good light olefin (C2-C4) selectivity and yield performance. These nanoparticles are then physically mixed with a zeolite, such as ZSM-5, to form a hybrid catalyst. The hybrid iron oxide catalyst was then activated in syngas at 10 bar and 290 °C for 24 h, and the catalyst performance was followed at 370 °C, 20 bar, and syngas flow with H2 / CO = 1. Where high activity (>90 Cmol.% CO conversion efficiency) was observed, the temperature and / or H2 / CO ratio were adjusted to maximize the light olefin yield.

[0089] 3) Hybrid nanostructure-supported, optionally X-promoted Fe-zeolite catalysts As another example, the present specification provides a method for preparing hybrid nanostructured Fe-zeolite catalysts, with or without X promotion, where X=Ni, Mn, Mg, Ca, La, Co, Li, K, Ce, or combinations thereof. The method for preparing nanosized Fe-based catalysts began by mixing an iron salt, such as Fe(NO3)3, and, in the case of X promotion, a salt of X, along with a surfactant, such as cetyltrimethylammonium bromide (CTAB), with deionized water. A NaOH solution was used to precipitate the iron and X from the solution. Tetraethyl orthosilicate (TEOS) was hydrolyzed to form the structure promoter in the form of SiO2, forming a silica matrix. The precipitate was collected by centrifugation without washing and dried in air before calcination at 500°C or higher for at least 2 hours. This method produces 4-5 nm sized X-promoted nanoparticles in a single precipitation, does not require a washing step to remove Na cations, and can provide good light olefin (C2-C4) selectivity, yield, and stability performance. The supported iron-based particles are then physically mixed with a zeolite such as ZSM-5 to form a hybrid catalyst. The hybrid catalyst is then activated in syngas at 10 bar and 290 °C for 24 hours, and the catalyst performance was then monitored in a syngas stream at 370 °C, 20 bar, and H2 / CO = 1. Where high activity (>90 Cmol.% CO conversion efficiency) was observed, the temperature and / or H2 / CO ratio were adjusted to maximize the light olefin yield.

[0090] <Example 2: Fe-zeolite hybrid catalyst (FeNa)> The Fe-zeolite hybrid catalyst (FeNa+HY) was prepared by mixing 10.81 g Fe(NO3)3·9H2O with 10 g CTAB in 400 ml deionized H2O to obtain a well-mixed solution. Then, 4 g NaOH in 80 ml deionized H2O was used to precipitate the iron in solution. The suspension was aged at room temperature for 5 min before collecting the precipitate by centrifugation. No washing of the precipitate was performed to leave Na as the promoter. The precipitate was then dried before calcination at 550 °C for 2 h. The Na-promoted FeNa catalyst was about 10 wt.%. The HY zeolite was then physically mixed with FeNa in a 1:1 weight ratio to obtain the hybrid catalyst.

[0091] The hybrid catalyst was transferred to a fixed bed reactor and reduced under flowing H2. It was activated with syngas at 290°C and 10 bar for 24 hours, and then the catalyst was characterized under flowing syngas with H2 / CO=1 at 370°C and 20 bar with a space velocity of 2,000 ml / gh. Where high activity (>90 Cmol.% CO conversion efficiency) was observed, the temperature and / or H2 / CO ratio were adjusted to maximize the light olefin yield.

[0092] High-resolution transmission electron micrographs were obtained with a field emission transmission electron microscope (TEM) (Tecnai G2 TF20 S-twin, FEI Company) operated at 200 kV. Figure 1A shows the TEM image of the FeNa catalyst, where the nanoparticles are clustered and can be clearly seen in the enlarged view of Figure 1B.

[0093] X-ray diffraction (XRD) spectra were measured at room temperature using a Bruker D8 Advance diffractometer (Bruker AXS GmbH, Germany) equipped with a Cu-Ka radiation source (λ = 1.54056 Å) operated at 40 kV and 30 mA. The samples were scanned using Bragg-Brentano geometry in the range 2θ = 10° to 90°. The crystalline phases of the Fe-based particles are shown in Figure 2, where the XRD patterns indicate a spinel structure that has yet to be identified. Figure 2A shows the XRD pattern of FeNa where precipitation occurred without aging at room temperature, showing a mixed phase of spinel and hematite (202), while the pattern aged at 70 °C for 16 h (204) shows a dominance of the spinel phase. Aging is thus seen to promote the formation of the spinel phase (FeNa2O4), i.e., as indicated by the absence of peaks near 33°, 35.8°, and 54°.

[0094] Figure 2B shows a comparison of the X-ray diffraction (XRD) pattern of FeNa (208) with the simulated pattern of FeNa2O4 (206). Figure 2B shows good correspondence between the measured and simulated patterns, with an error range of about ±1% in peak positions. The measured spectrum was smoothed to improve the signal-to-noise ratio, and LiMn2O4 was used as the starting structure, with Li substituted for Na and Mn substituted for Fe. A periodic unit cell was constructed and a discrete Fourier transform (DFT) was performed to obtain the ground state using Quantum Espresso. The XRD pattern of FeNa2O4 was then simulated using Visualizaton for Electronic and Structural Analysis (VESTA).

[0095] Fe K-edge X-ray absorption spectra (XAS) were recorded at the Extended-Area X-ray Absorption Fine Structure for Catalysts (XAFCA) beamline at the Singapore Synchrotron Fight Source. The samples were first mixed with boron nitride and thoroughly ground, then pressed onto small circular disks with a diameter of 1 cm. The XAS spectra of the catalysts were then measured at room temperature in He.

[0096] Extended X-ray absorption fine structure analysis (EXAFS) was performed using Athena software. In the EXAFS of FeNa (302) in Figure 3, the Fe-O coordination peak (308) is observed at a radial distance of 1.4 Å, and the first Fe-Fe coordination peak (310) is observed at 2.6 Å. The second Fe-Fe coordination peak (312) is observed at 3.1 Å, which is typical of Fe3O4 (304) and exists as a shoulder in Fe2O3 (304) due to the low Fe content in the chemical composition. Figure 3 shows the absence of the Fe-Fe coordination peak (312) in FeNa (Fe2O3-Na) (302) that is typically seen in Fe2O3 (306) and Fe3O4 (304), suggesting that the Fe atom has been replaced by another element, hypothetically Na. Elemental composition analysis of the FeNa catalyst was performed using electron dispersive X-ray spectra, which are shown in Figure 4. The EDS shows a homogeneous distribution from the contributions of Fe (Figure 4A), Br (Figure 4B), Na (Figure 4C), and O (Figure 4D). The EDS was performed using a field emission scanning electron microscope (FE-SEM, JEOL JSM 6700) with a beam energy of 5 keV and an Oxford instrument EDS system.

[0097] Table 1 shows the properties of FeNa and FeNa combined with various zeolites at 370°C, 20 bar, H2 / CO=1, and gas hourly space velocity (GHSV) of 2,000 ml / gh.

[0098] Specifically, FeNa catalyst was pelletized at 40 kN and sieved to 250-500 pm particles. 0.5 g of FeNa catalyst was then mixed with SiC in a 1:1 volume ratio and then fixed in a fixed bed reactor for testing. Reduction was carried out at 600°C for 6 hours in H2 and atmospheric pressure at a space velocity of 2000 ml / (gh). Activation was carried out at 290°C for 24 hours in CO and H2 with H2 / CO ratio=2 at 10 barg and a space velocity of 2000 ml / (gh). CO reaction was carried out at 370°C in CO and H2 with H2 / CO ratio=2 at 20 barg and a space velocity of 2000 ml / (gh).

[0099] The reaction data shown in Table 1 shows an improvement in activation time (from 40 to 10-16 hours) and also a general improvement in the selectivity of C2-C4 hydrocarbons. HY zeolites show that they change the hydrocarbon distribution by cracking C5+ to shorter chain hydrocarbons. Furthermore, the olefinicity also improved when FeNa was combined with, for example, HY(80) and ZSM-5(80). Higher olefinicity can be obtained with both HY and ZSM-5 zeolites with higher SiO2 to Al2O3 ratios. As shown in Table 1, the yield of light olefins with FeNa+HY(80) is improved over FeNa alone. This shows that activity, selectivity, and olefinicity can be tuned by blending different zeolites and catalysts. Table 1 shows the properties of the hybrid FeNa+ zeolite combination in FTO at 370°C, 20 bar, 2000 ml / gh, H2 / CO=1.

[0100] [Table 1]

[0101] Similar hybrid systems reported in the art typically use ZSM-5 for its shape and size selectivity and target the production of paraffinic hydrocarbons in the gasoline range. In contrast, the present system aims to maximize the selectivity and yield of light olefins. A comparison with similar hybrid systems is shown in Table 2. Olefinicity is dramatically improved with the hybrid FeNa-ZSM-5 system.

[0102] The properties of the combination FeNa+ZSM-5 compared to similar systems in the art are shown in Table 2. The FeNa+ZSM-5 reaction was carried out at 370°C, 20 bar, 2000 ml / gh and H2 / CO=1.

[0103] [Table 2]

[0104] In Table 2 sample used Fe and Cu nitrates and precipitated with NaOH (except for Fe-Cu-K / ZSM-5 (25) which was precipitated with KOH and Fe+ZSM-5 (80) which was precipitated with NH4OH). The samples were then mixed with ZSM-5 for testing. FeNa (present catalyst) is Fe2O3-Na, Fe (comparative) is pure FeO3, and Fe-Cu (comparative) is a mixture of iron and copper oxides.

[0105] Example 3: Mn-promoted Fe-zeolite hybrid catalyst Mn-promoted Fe-zeolite hybrid catalyst (FeNa+HY) was prepared by first synthesizing Mn-promoted FeNa (FeNa-Mn) catalyst by mixing 9.73 g Fe(NO3)3·9H2O and 0.67 g Mn(NO3)2·4H2O with 10 g CTAB in 400 ml deionized H2O to obtain a well-mixed solution. Next, 4 g NaOH in 80 ml deionized H2O was used to precipitate the metals in solution. The suspension was aged at room temperature for 5 min before collecting the precipitate by centrifugation. No washing of the precipitate was performed to leave Na as the promoter. The precipitate was then dried before calcination at 550 °C for 2 h. The Na-promoted FeNa-Mn catalyst was about 10 wt.%, with an Fe to Mn ratio of about 9. The HY zeolite was then physically mixed with FeNa-Mn in a 1:1 volume ratio to obtain the hybrid catalyst.

[0106] The hybrid catalyst was transferred to a fixed bed reactor and reduced under flowing H2. An activation protocol of flowing syngas with H2 / CO=1 at 10 bar and 290°C for 24 hours was used to activate the catalyst. Finally, the loading step was monitored by tracing the properties under flowing syngas with H2 / CO=1 at 370°C, 20 bar and space velocity of 2,000 ml / gh. Where high activity (>90 Cmol.% CO conversion efficiency) was observed, the temperature and / or H2 / CO ratio were adjusted to maximize the light olefin yield.

[0107] Figure 5 shows the electron dispersive X-ray spectrum (EDS) mapping of the constituent atoms of the FeNa-Mn catalyst. The image shows good dispersion and homogeneous distribution of Fe (Figure 5A), Br (Figure 5B), Na (Figure 5C), and Mn (Figure 5D), as well as oxygen inclusions present in the form of oxides (Figure 5E). X-ray photoelectron spectroscopy (XPS) was performed on a VG ESCALAB 250 spectrometer equipped with a monochromatic MgKa radiation source. All binding energies were line-aligned with reference to C1 at 284.6 eV.

[0108] Figure 6 shows the XPS spectrum of FeNa with Br, and according to the binding energy, it is suggested that Br exists in the form of bromate and may be reduced to bromide during the reduction process of H2. The reduced bromide may play a role in the formation of Fe5C2. Table 3 shows the properties of FeNa-Mn combined with and without HY zeolite at 370°C, 20 bar, H2 / CO=1, and gas hourly space velocity (GHSV) of 12,000 ml / gh.

[0109] [Table 3]

[0110] Table 3 shows that the hybridization with HY zeolite reduced the activation time by six times, improved the FTO reaction, and increased the proportion of light hydrocarbons.

[0111] Example 4: FeNa catalyst in a silica matrix Figure 7 shows FeNa catalyst in a silica matrix Figure 2 Transmission electron microscope (TEM) micrograph of Fe-based nanoparticles showing good dispersion throughout the 90 wt.% silica matrix.

[0112] Typically, 10.81 g of Fe precursor Fe(NO3)3·9H2O was dissolved in 400 ml of deionized (DI) H2O and mixed with 10 g of cetyltrimethylammonium bromide (CTAB). The precipitation reagent was 4 g of NaOH dissolved in 80 ml of DI H2O, and then 60 ml was added instead of the usual 80 ml to obtain spherical Fe particles by pH control. It should be noted that precipitation with 80 ml of NaOH solution results in rod-like Fe structures. The encapsulation of the iron catalyst was first performed by preparing the unsupported catalyst according to Example 2 up to the precipitation step (e.g., before the drying and calcination steps in air) followed by the addition of SiC8H according to the required weight percentage. 20Add 10Fe2O3 (TEOS) to SiO2 containing 10 wt% Fe2O3. For example, 10Fe2O3 in SiO2 required 143 ml of TEOS dissolved in 200 ml of ethanol. TEOS was hydrolyzed for at least 8 h before centrifugation of the mixture and drying at 80 °C for 48 h.

[0113] <Example 5: Comparison of characteristics> The properties of the catalyst of the present invention were compared with those of the benchmark comparative examples. Table 4 shows the properties of FeNa, FeNa+HY, and 10FeNa@SiO2, as well as the comparative example Fe(Na+S) / CNF. [Table 4]

[0114] The comparative examples were made by impregnation method and supported by carbon nanofibers (CNF), whereas the catalysts of the present invention were formed by precipitation.

[0115] It is observed that the catalysts of the present invention in Table 4 (first and second columns) have a better olefin ratio (O / (O+P)) compared to the comparative example (fourth row), and it can be seen that the catalysts of the present invention have a significantly higher olefin ratio.

[0116] The above is further supported by FIG. 8 showing the light olefin ratio (O / O+P) vs. CO conversion of the catalyst of the present invention FeNa (Fe2O3-Na) activated under different conditions. The catalyst performance was shown to be improved by parameter optimization. FIG. 9 further shows a comparison of long-term stability between Fe2O3 and Fe / CNF from the prior art. The catalyst of the present invention continues to improve its performance after 170 hours, whereas the performance of the benchmark (prior art) catalyst dropped to less than half of the initial value after 100 hours.

[0117] Table 4, Figure 8, and Figure 9 show that the catalyst of the present invention achieved the milestone of 20% light olefin (LO) yield even when the olefin selectivity was not as high as the comparative example, and also when the activity was not as high as the comparative example.

[0118] Example 6: Olefins from CO The use of the catalyst for the conversion of CO2 to olefins was also investigated. A FeNa catalyst washed with deionized water was pelletized at 40 kN and heated at 250–500 μm The catalyst was sieved into 1000 ml / (gh) particles. 0.5 g of FeNa catalyst was then mixed with SiC in a 1:1 volume ratio and then packed into a fixed bed reactor for testing. Reduction was carried out at 580°C for 6 hours in H2 and atmospheric pressure at a space velocity of 2000 ml / (gh). Activation was carried out at 300°C for 4 hours in CO and H2 with a H2 / CO ratio=2 at 10 barg and a space velocity of 2000 ml / (gh). CO2 reaction was carried out at 350°C in CO2 and H2 with a H2 / CO2 ratio=3 at 15 barg and a space velocity of 5500 ml / (gh).

[0119] The catalytic activity of the FeNa catalyst in the CO2 to olefin reaction is shown in Table 5.

[0120] Table 5 shows the catalytic activity of FeNa catalyst in CO2 to olefin reaction, where X(CO2) indicates the conversion of CO2, and S(CH4) and S(CO) indicate the selectivity to CH4 and CO, respectively.

[0121] [Table 5]

[0122] Above, the FeNa catalyst achieved a light olefin yield of 10.8% at 46% CO2 conversion, showing a very high proportion of olefins in C2-C4 and relatively low selectivity to CH4 and CO. It was shown that optimization for further improvement of olefin yield is possible.

[0123] <Industrial Applicability> The hybrid nanoparticle iron catalysts described herein may be used in Fischer-Tropsch synthesis to convert CO2 or a mixture of CO and CO2 with H2 as a feedstock to produce light olefins. The catalysts are useful in the synthesis process of light olefins, the process has a high selectivity to light olefins over methane, longer chain olefins or paraffins, and the catalyst has a significantly shorter activation time. The method of preparing the catalyst described herein includes co-precipitating the iron nanoparticle catalyst with a basic salt solution to prepare the catalyst, which can facilitate the preparation of the catalyst. Furthermore, the process described herein can be used to prepare light olefins, the process has a high selectivity to light olefins. The catalysts are useful in the conversion of CO and / or CO2 as a feedstock to other hydrocarbons, such as alcohols and C5+ hydrocarbons. Various other modifications and applications of the invention will be apparent to those skilled in the art upon reading the foregoing disclosure without departing from the spirit and scope of the invention, and all such modifications and applications are intended to be included within the scope of the appended claims.

Claims

1. 1. A hybrid iron nanoparticle catalyst for a Fischer-Tropsch synthesis reaction, comprising: i) iron; at least one metal M selected from the group consisting of alkali metals, alkaline earth metals, transition metal elements of groups 3 to 7 and 9 to 11 of the periodic table, lanthanides, and combinations of these elements; 30 to 70 wt. % of the total weight of the catalyst, ii) 70 to 30 wt.% of an aluminosilicate or silicoaluminophosphate zeolite based on the total weight of the catalyst; The nanoparticles have a diameter of 2 to 50 nm; the total weight percentage of the nanoparticles and the zeolite is 100 wt.%; The iron-containing nanoparticles further comprise a halogen oxide.

2. 1. A hybrid iron nanoparticle catalyst for a Fischer-Tropsch synthesis reaction, comprising: i) iron; at least one metal M selected from the group consisting of alkali metals, alkaline earth metals, transition metal elements of groups 3 to 7 and 9 to 11 of the periodic table, lanthanides, and combinations of these elements; 30 to 70 wt. % of the total weight of the catalyst, ii) 70 to 30 wt.% of an aluminosilicate or silicoaluminophosphate zeolite based on the total weight of the catalyst; The nanoparticles have a diameter of 2 to 50 nm; the total weight percentage of the nanoparticles and the zeolite is 100 wt.%; The iron-containing nanoparticles are SiO 2 Dispersed in the matrix, the catalyst.

3. 3. The catalyst according to claim 1 or 2, wherein the zeolite is SAPO11 or SAPO34.

4. 4. The catalyst of claim 1, wherein the iron-containing nanoparticles further comprise an element of a transition metal from groups 3 to 7 and 9 to 11 of the periodic table.

5. 5. The catalyst according to claim 1 , wherein the metal M constitutes 10 to 50 wt.% of the weight of the iron-containing nanoparticles.

6. The nanoparticles have the formula FeM 2 O 4 6. The catalyst according to claim 1 , having a spinel crystal phase represented by:

7. The zeolite is a pentasil zeolite or a faujasite zeolite, or 3. The catalyst of claim 1 or 2, wherein the zeolite is selected from the group consisting of zeolite X, ZSM-5, zeolite Y, ZSM-12, ZSM-22, and HY zeolite.

8. 8. The catalyst according to claim 1, wherein the molar ratio of alumina to silica in the zeolite is from 1:2 to 1:

90.

9. 9. The catalyst according to claim 1, wherein the weight ratio between the zeolite and the nanoparticles comprising iron is from 1:0.5 to 1:

10.

10. 2. The catalyst of claim 1, wherein the halogen oxide is present in an amount of 0.1 to 50 wt.% of the weight of the nanoparticles.

11. 5. The catalyst of claim 4, wherein the molar ratio of iron to said transition metal is from 1:1 to 50:

1.

12. A method for preparing a hybrid nanoparticle iron catalyst for a Fischer-Tropsch synthesis reaction, comprising the steps of: i) mixing a solution comprising an iron salt with an aqueous surfactant comprising an oxide halogen to form a mixture; ii) adding a solution of a basic salt comprising a salt of an element selected from the group consisting of alkali metals, alkaline earth metals, transition metal elements of groups 3 to 7 or 9 to 11 of the periodic table, lanthanides, and combinations thereof to the mixture of step (i) to produce a precipitate; iii) heating the precipitate of step (ii) in the presence of air or oxygen; and iv) mixing the precipitate of step (iii) with an aluminosilicate or silicoaluminophosphate zeolite to obtain a hybrid iron catalyst.

13. A method for preparing a hybrid nanoparticle iron catalyst for a Fischer-Tropsch synthesis reaction, comprising the steps of: i) mixing a solution comprising an iron salt with an aqueous surfactant to form a mixture; ii) adding a solution of a basic salt comprising a salt of an element selected from the group consisting of alkali metals, alkaline earth metals, transition metal elements of groups 3 to 7 or 9 to 11 of the periodic table, lanthanides, and combinations thereof to the mixture of step (i) to produce a precipitate; iii) heating the precipitate of step (ii) in the presence of air or oxygen; iv) mixing the precipitate of step (iii) with an aluminosilicate or silicoaluminophosphate zeolite to obtain a hybrid iron catalyst; Prior to the step (iii) of heating the precipitate of step (ii), iron-containing nanoparticles are added to a SiO 2 A method for distributing in a matrix.

14. 14. The method of claim 12 or 13, wherein the salt of the element comprises a hydroxide, carbonate, or bicarbonate anion.

15. 15. The method according to any one of claims 12 to 14, wherein the molar ratio of the iron to the element of the basic salt is from 1:2 to 1:

25.

16. 16. The method of any one of claims 12 to 15, wherein the heating step of step (ii) is carried out at a temperature of from 300°C to 600°C or for a time of from 1 to 10 hours.

17. the iron salt is a divalent iron salt or a trivalent iron salt, or 17. The method of any one of claims 12 to 16, wherein the iron salt comprises an anion selected from the group consisting of nitrate, chloride, fluoride, bromide, iodide, phosphate, pyrophosphate and perchlorate.

18. the surfactant is an ionic surfactant, or 18. The method of any one of claims 12 to 17, wherein the surfactant comprises an anion selected from the group consisting of halides, sulfonates, sulfates, phosphates and carboxylates.

19. 19. The method of any one of claims 12 to 18, wherein the molar ratio of iron to the surfactant is from 1:0.5 to 1:

15.

20. 20. The method of claim 12, further comprising recovering the precipitated nanoparticle catalyst and drying the precipitated nanoparticle catalyst in air prior to step (iii).

21. 21. The method of claim 20, wherein recovery of the precipitated nanoparticle catalyst is performed by centrifugation and / or filtration.

22. 22. The method of any one of claims 12 to 21, further comprising adding a solution of a salt of a transition metal to the mixture of step (i) prior to step (ii).

23. 22. The method of any one of claims 12 to 21, further comprising introducing the mixture of step (i) into a solution of silicate prior to step (ii).

24. 24. The method of claim 23, wherein the silicate comprises an alkoxy group of 2 to 15 carbon atoms.

25. 25. The method of claim 23 or 24, wherein the molar ratio of iron to said silicate is from 1:1 to 1:

50.

26. A process for producing light olefins, comprising: i) heating the catalyst according to any one of claims 1 to 11 in the presence of a gas comprising one or more carbon oxides and hydrogen to activate the catalyst; ii) contacting the catalyst activated in step (i) with a gaseous stream comprising one or more carbon oxides and hydrogen to partially or completely convert said one or more carbon oxides to said light olefins, The light olefin contains from 2 to 4 carbon atoms; The process wherein methane is not included in said light olefins or comprises less than 20% of said light olefins.

27. 27. The process of claim 26, wherein step (i) is carried out at a temperature of from 200° C. to 350° C., or wherein step (ii) is carried out at a temperature of from 200° C. to 450° C., or wherein step (i) is carried out at a pressure of from 5 to 30 bar, or wherein step (ii) is carried out at a pressure of from 5 to 50 bar.

28. 28. The process according to claim 26 or 27, wherein the space velocity of the gas fluid in step (ii) is from 1500 ml / gh to 5000 ml / gh.

29. 29. The process of any one of claims 26 to 28, wherein the molar ratio of hydrogen to the one or more carbon oxides of the gas is from 4:1 to 1:

3.

30. 30. The process of any one of claims 26 to 29, further comprising, prior to step (i), reducing the catalyst of any one of claims 1 to 11 by contacting the catalyst with a stream of hydrogen gas.

31. 31. The process of any one of claims 26 to 30, wherein the carbon oxide of the gaseous fluid in step (ii) is carbon dioxide.

Citation Information

Patent Citations

  • Nano catalyst for producing low carbon olefin hydrocarbon using synthesis gas and preparation method thereof

    CN101396662A

  • The liquid fuel is converted into a synthesis gas catalyst and method for improving motor - the motor -

    JP1986502544A

  • The liquid fuel to the - motor - meter high synthesis gas conversion

    JP1986502897A

  • Production of olefin

    JP1990000121A

  • Carrier for selective synthesis of high-quality kerosene fraction from syngas, its catalyst, and its preparation method

    JP2018524156A